The integration between re-engineering and modern Approaches to reducing costs in the management of change - حسين, نادية شاكر (Journal of Economics and Administrative Sciences, 2012)
The entrance process re-engineering one of the main entrances of administrative and technology appropriate to keep pace with scientific progress and the continuing changes in business environment and for the purpose of achieving the goal sought by the organizations in the pursuit of rapid developments and renewable energy in the market competition by changing its operations and activities of the radical change which contributes to an effective contribution to reducing the cost of product or service taking into account the quality improvement in the management of change to keep the increase value and speed of placing on the market to meet customer needs and desires to achieve and attain the goal of growth and stability in the market under the umbrella of integration between the entrance re-engineering of processes and approaches of contemporary with each other, which is due the positive impact on reducing costs more if the organization has been the use of the entrance of a particular individual because of integration and interdependence relations among the entries.